Passivation and red-ox processes of refractory metals in carbamide-chloride melt - Tumanova N.; Volkov S.; Kochetova S.; Triphonova T.; Buryak N. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electrochemical behavior of refractory metals (Pt, Pd, W, Ti, Nb, Ta) in the low temperature carbamide-NH4Cl melt (texp=120 oC) and the structure of complex ions formed after anodic dissolution have been studied by cyclic voltammetry and spectroscopic methods. The features of the mechanism of metal electrodissolution and possibilities of the cathodic reduction of complexes formed in the melt are presented. A possible correlation between passivation processes on the metal surface, the mechanism of electrodissolution, composition of complexes and the electrochemical activity of metals and their ions are discussed. The data obtained reflect the possibilities to use the carbamide-NH4Cl melt for practical purposes in electroplating and electropolishing.